Optimization of PSWAN in terms of cost and bandwidth - Aadil Gani Ganie (International Journal of Information Technology and Business, 2022)
PSWAN is an internetworking project undertaken by Govt. of India at Pondicherry. It covers a vast area, under it there are various state headquarters and district headquarters. Approximately 3000 systems are using its internet services. Since the number of systems are more and the bandwidth required is less so optimization was needed. Optimization was required without hardware modifications, so we defined some of the parameters through which we can achieve the optimization of this network, these parameters are 1. Type of protocol 2. Type of Topology 3. Access policies 4. Load balancing 5. Traffic bottle neck 6. Bandwidth utilization. To make the network cost effective, some small networks were moved to broadband network so that bandwidth usage can be mitigated and consequently network will get optimized. Since this project (PSWAN) is using the CISCO devices only so it was easy to simulate the network, we used OPNET simulator as it is precise than other simulators. First the operational network was simulated and then the proposed one, proposed model showed evident positive results. The simulation tool used is Opnet. OPNET is extensive and powerful simulation software with wide variety of capabilities. It enables the possibility to simulate entire heterogeneous networks with various protocols